Masjid Bandaraya Kuching Sarawak Tahun 1839-2019 - Nur Hidayah Binti Abd.Rahim; Nyong Teguh Eka Santosa (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2021)
Abstract: This study is to find out the development of Kuching Bandaraya Mosque Sarawak and its function to the community. Islam in Kuching Sarawak was carried by the Sultanate of Brunei in the 15th century. The historical method used here consists of heuristics, verification, interpretation, and historiography. The discussion relates to a political history in which the theory of power dominance is applied. The results of this study indicate that the Bandaraya mosque was awakened in 1839. Its development passed through several periods. Keywords: Kuching Bandaraya Mosque, Sarawak, Malaysia, the Sultanate of Brunei